NV-centers in SiC: A solution for quantum computing technology? - Khazen, Khashayar; von Bardeleben, Hans Jurgen (Frontiers in Quantum Science and Technology, 2023)
Spin S=1 centers in diamond and recently in silicon carbide, have been identified as interesting solid-state qubits for various quantum technologies. The largely-studied case of the nitrogen vacancy center (NV) in diamond is considered as a suitable qubit for most applications, but it is also known to have important drawbacks. More recently it has been shown that divacancies (VSiVC)° and NV (VSiNC)- centers in SiC can overcome many of these drawbacks such as compatibility with microelectronics technology, nanostructuring and n- and p-type doping. In particular, the 4H-SiC polytype is a widely used microelectronic semiconductor for power devices for which these issues are resolved and large-scale substrates (300mmm) are commercially available. The less studied 3C polytype, which can host the same centers (VV, NV), has an additional advantage, as it can be epitaxied on Si, which allows integration with Si technology. The spectral range in which optical manipulation and detection of the spin states are performed, is shifted from the visible, 632nm for NV centers in diamond, to the near infrared 1200-1300nm (telecom wavelength) for divacancies and NV centers in SiC. However, there are other crucial parameters for reliable information processing such as the spin-coherence times, deterministic placement on a chip and controlled defect concentrations. In this review, we revisit and compare some of the basic properties of NV centers in diamond and divacancies and NV centers in 4H and 3C-SiC.